2017
DOI: 10.1080/02770903.2016.1274402
|View full text |Cite
|
Sign up to set email alerts
|

Parental coping, depressive symptoms, and children's asthma control and school attendance in low-income, racially, and ethnically diverse urban families

Abstract: Parents' secondary control and disengagement coping are related to children's asthma outcomes. Secondary control coping may support parents' mental health and children's asthma control in low-income urban families.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 43 publications
1
23
0
Order By: Relevance
“…32 Further, studies in other illness groups have shown that parents with higher education levels have endorsed employing secondary control coping mechanisms by reframing their view of stressful situations that are out of their control. 33 As such, it is surprising to find that study participants with higher parental education endorsed poorer family functioning. We hypothesize that this may be unique to pOHT.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…32 Further, studies in other illness groups have shown that parents with higher education levels have endorsed employing secondary control coping mechanisms by reframing their view of stressful situations that are out of their control. 33 As such, it is surprising to find that study participants with higher parental education endorsed poorer family functioning. We hypothesize that this may be unique to pOHT.…”
Section: Discussionmentioning
confidence: 96%
“…Higher parental education has been shown to be associated with protective factors like increased coping and guidance seeking 32 . Further, studies in other illness groups have shown that parents with higher education levels have endorsed employing secondary control coping mechanisms by reframing their view of stressful situations that are out of their control 33 . As such, it is surprising to find that study participants with higher parental education endorsed poorer family functioning.…”
Section: Discussionmentioning
confidence: 99%
“…A child's chronic illness, such as asthma, induces excessive stress and physical and psychological burdens to parents and the whole family (Ekim and Ocakci 2016;Kim and Yoo 2007;Silva et al 2015). At the same time, caregiver stress is known to contribute to the development and course of child asthma, with depression in the parent predicting poorer asthma control (Celano 2006;Rioseco et al 2017;Rodriguez et al 2017;Wood et al 2015). Depression correlates with parental style and ability to cope with stressors.…”
Section: Parental Burdenmentioning
confidence: 99%
“…Depression is common among parents of children with asthma, expressing itself in a variety of ways, through impairing parental coping with daily life stressors and with the challenges of the child's asthma. Parental depression is associated with more asthma symptoms, increased healthcare use, poor asthma management, and missed medical appointments (Avcil et al 2018;Rioseco et al 2017;Rodriguez et al 2017;Wood et al 2015). It also contributes to negative affect and irritability, hopelessness, anxiety, and distressed relationships between the parent and child and increases the likelihood of authoritarian, hostile, and rejecting styles of parenting.…”
Section: Sources Of Stress Parent Mental Health Problemsmentioning
confidence: 99%
See 1 more Smart Citation